SYNTACTICAL ERROR ANALYSIS OF ABSTRACT THESIS BY UNDER GRADUATE STUDENTS OF SEKOLAH TINGGI BAHASA ASING (STIBA)-IEC BEKASI - Resmisari, Diah; Rusman Putri, Herdas Prayunas; Abdulloh, Abdulloh; Sitepu, Julyanta Br.Sitepu Br (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2023)
This study is motivated by observation data, which shows that the majority of students believe writing is difficult. To address this issue, the author conducts research to determine the types of syntactical errors, the dominant type of syntactical errors, and the factors that influence the students' syntactical errors. The descriptive qualitative research method is used in this study. The data are drawn from abstract theses written by undergraduate students at Sekolah Tinggi Bahasa Asing (STIBA)-IEC Bekasi from 2017 to 2019. The research results have been categorized according to James' (1998) classification of syntactical errors proposed in Error in Language Learning and Use. The analysis reveals the existence of five distinct types of syntactical errors, namely omission, addition, misformation, misordering, and blend. Among these, misformation emerges as the predominant type of syntactical error committed by the students. Furthermore, the occurrence of these syntactical errors is found to be influenced by both inter-lingual and intra-lingual factors.